PENGENDALIAN ASET NIRWUJUD DALAM MANAJEMEN SISTEM IRIGASI TINGKAT TERSIER - , Nugroho Tri Waskitho, Ir.,MP.; , Prof. Dr. Ir. Sigit Supadmo Arif, M.Eng, ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Irrigation was an important sector of the agricultural development, but it had many problems. The problems were 23% irrigation networks were damaged, only 11% of irrigation systems provided sufficient water availability, irrigation management was inefficient, and new paradigm had not been implemented well yet. These problems were caused by the low quality of intangible assets. The research aimed at (i) finding the basic of controlling intangible assets in irrigation system tertiary level, (ii) building the model of controlling intangible assets in irrigation system tertiary level, and (iii) investigating intangible assets in irrigation system tertiary level. The research method employed four stages. The first stage was building the concept of controlling intangible assets in irrigation system based on knowledge management. The second stage was building the model of controlling intangible assets in irrigation system using neuro-fuzzy principles. The model linked three sub models: (i) knowledge management, (ii) intangible assets, and (iii) performance of irrigation system. The knowledge management comprised four variables: (i) learning organization, (ii) principles of organization, (iii) policy and strategy of organization, and (iv) information and communication technology. Intangible assets comprised five variables: (i) moral intelligence, (ii) emotional intelligence, (iii) creativity attitude, (iv) institutional culture, and farmer participation. Performance of irrigation system comprised one variable: effectiveness. The third stage was evaluating the model of controlling intangible assets in irrigation system management in Sapon irrigation system in Kulon Progo, Yogyakarta. Data were taken by questionnaire on Water Use Associations or Kuwowo in upstream, middlestream, and downstream of irrigation area. Data were analyzed by Adaptive Neuro Fuzzy Inference System. Performance of the model was evaluated by Correlation Coefficient, Mean Absolute Percentage Error (MAPE) dan Root Mean Square Error (RMSE). The fourth stage was investigating intangible assets in irrigation system of Mejing in Bantul, Yogyakarta and Molek in Malang, East Java using knowledge management approach. The result of the research indicated that the concept of controlling intangible assets in tertiary level irrigation system management had built. The concept stated that performance of tertiary level irrigation system depended on balancing of tangible assets and intangible assets. Knowledge management could be used for building the concept of controlling intangible assets in irrigation system management. Model of controlling intangible assets in tertiary level irrigation system management which using neuro fuzzy predicted intangible assets and effectiveness of tertiary level irrigation system well. Knowledge management influented intangible assets in tertiary level irrigation system tertiary level irrigation system. Intangible assets influented effectiveness of tertiary level irrigation system. Parameter of learning organization was the most sensitive in influenting moral intelligence and creative attitude. Parameter of policy and strategy was the most sensitive in influenting emotional intelligence, institutional culture and farmer participation. Parameter of institutional culture was the most sensitive in influenting effectiveness of tertiary level Molek irrigation system. Parameter of creative attitude was the most sensitive in influenting effectiveness of tertiary level Mejing irrigation system Parameter of moral intelligence, emotional intelligence and farmer participation were the most sensitive in influenting effectiveness of tertiary level Sapon irrigation system. Intangible assets in tertiary level irrigation system were good. Learning organization in tertiary level Mejing irrigation system was good, in tertiary level Sapon irrigation system was very good, and in tertiary level Molek irrigation system was very poor.